2008
DOI: 10.1177/1098214008318798
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Immersio Approach to Evaluation Capacity Building

Abstract: The purpose of this article is to describe a new collaborative immersion approach for developing evaluation capacity that was used in kindergarten through Grade 12 (K-12) schools and to place this new approach on a continuum of existing capacity-building methods. The continuum extends from individualistic training-oriented methods to collaborative real-world methods of building evaluation capacity. The strengths and weaknesses of various evaluation capacity building methods are analyzed and critiqued. Included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…Moreover, the study contributes to literatures on ALS and nonformal education as it sheds the light on the present status of ALS, especially in the Philippines in terms of the promotion of 21st-century skills among its clients and enrollees. More importantly, the study gave insights and recommendations to previous researches and studies with regard to the evaluation and assessment of nonformal education (Huffman et al, 2008;Isaacs et al, 2010;Walahoski & Suzanne, 2012) such as the ALS program of the Philippines (Dela Rosa, 2015;Mercado, 2005;Oracion, 2002), especially in terms of assessing the 21st-century skills of nonformal education such as the ALS learners (Guerrero, 2007;Rogers, 2005).…”
Section: Conclusion and Implications For Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study contributes to literatures on ALS and nonformal education as it sheds the light on the present status of ALS, especially in the Philippines in terms of the promotion of 21st-century skills among its clients and enrollees. More importantly, the study gave insights and recommendations to previous researches and studies with regard to the evaluation and assessment of nonformal education (Huffman et al, 2008;Isaacs et al, 2010;Walahoski & Suzanne, 2012) such as the ALS program of the Philippines (Dela Rosa, 2015;Mercado, 2005;Oracion, 2002), especially in terms of assessing the 21st-century skills of nonformal education such as the ALS learners (Guerrero, 2007;Rogers, 2005).…”
Section: Conclusion and Implications For Further Researchmentioning
confidence: 99%
“…Recent trends in research stressed the need in evaluating the effectiveness of nonformal education programs (Huffman, Lawrenz, & Thomas, 2008;Isaacs, Macomber, Rennane, & Steuerle, 2010;Walahoski & Suzanne, 2012), such as the ALS Program of the Philippines (Dela Rosa, 2015;Mercado, 2005;Oracion, 2002). The use of effective evaluation of such programs plays a critical role in revealing its outcomes specially in terms of assessing if the objectives of the programs are really met (Braverman & Arnold, 2008;Castleberry & Enger, 1998;Clavijo, Flemming, Hoerman, Toal, & Johnson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While the framework Arnold proposes was effective, most youth organizations do not have an internal evaluator to do this work. Others have proposed frameworks that are collaborative efforts between external evaluators and program staff that have demonstrated ECB effectiveness (Garcia-Itiarte, Suarez, Balcazar, Taylor-Ritzler, & Luna, 2010;Huffman, Thomas, & Lawrenz, 2008).…”
Section: Evaluation Capacity Building Through Youth Participatory Evamentioning
confidence: 99%
“…This has been the motivation behind trainings at all levels in M&E cycle. Since evaluation competence could be determined by factors such as, skills, knowledge, and attitudes of individuals towards M&E, training of individuals to enhance them is key as this offers skills and techniques that one must learn to conduct quality evaluation (Huffman et al, 2008). This need for developing professionalism in M&E has been necessitated by the fact that only few personnel in project management have a background in evaluation as highlighted by TaylorPowell and Boyd(2008).The biggest number of these have an advanced degree in social sciences and may have completed courses in research methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…M&E professional development would include training individuals in skills and techniques that help one to conduct quality evaluations. Training is used to enhance knowledge, skills, and confidence so that project staff are able to conduct adequate evaluations of their own projects (Taylor-Powell & Boyd;2008;Huffman, Thomas & Lawrenz, 2008). Other professionalism development activities considered in this study were suggested by TaylorPowell and Boyd (2008) and they include thematic training, technical assistance in M&E, collaborative evaluation activities, mentoring and coaching and establishing communities of practice enhance professionalism in M&E. Arguably these are activities that facilitate learning that improve knowledge and skills of M&E practitioners.…”
Section: Introductionmentioning
confidence: 99%